2022
DOI: 10.1155/2022/7740313
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of Sino‐Russian Media Cooperation and the Construction of International Online Public Opinion Discourse under the Dual Influence of Ecological and Online Environments

Abstract: In the context of traditional media, the media can dominate the topic and composition of public opinion, but in the context of the convergence of online media, the dominance of public opinion has gradually evolved from the direction of the coexistence of single items and pluralism, especially from the international level. In other words, the construction of the comprehensive strategic writing partnership between China and Russia in the new era has given a new orientation and connotation to the bilateral relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%